Principles and Paradigms of Inter‐State Law: A Specialized Study of the Law of War, Human Rights, and Commercial Jurisdictions in the Context of Classical Islamic Texts - Hafiz Amir Shahzad; Muhammad Hammad Saeed (Journal of Religion and Society, 2025)
This study offers a focused and comprehensive analysis of the principles and paradigms of inter-state law, particularly on the domains of the law of war (qānūn al-ḥarb), human rights, and commercial jurisdictions, within the hermeneutical framework of classical Islamic texts. Grounded in Qur’anic injunctions, Prophetic traditions (ḥadīth), and the historical practices (sīra) of the early Muslim community, the research examines how traditional jurists conceived interstate relations (siyar), restricted the use of force, and safeguarded individual and collective rights in contexts of conflict and commerce. The study juxtaposes these classical doctrines with modern international legal norms to highlight convergences, divergences, and the interpretive challenges inherent in recontextualizing medieval Islamic legal thought for contemporary global order. Keywords: Islamic international law, classical jurisprudence, law of war (qānūn al-ḥarb), human rights, commercial jurisdiction, siyar, Qur’an and ḥadīth, comparative law.